Hypnotherapy Intervention on Pain Scale Level of Arteriovenous Fistula Cannulation in Haemodialysis Patients with Chronic Renal Failure - Ahmad Syaripudin (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the effectiveness of hypnotherapy intervention on the level of pain scale of arteriovenous fistula cannulation installation in haemodialysis patients with chronic renal failure. This research method is quasi experimental (one pre-post group desaign). The sample of this study was chronic renal failure patients in arteriovenous fistula cannulation access insertion totalling 45 respondents using total sampling technique. The results obtained before hypnotherapy were 11 respondents (24.4%) experienced a mild pain scale level response, 34 people (75.66%) experienced a moderate pain scale level response while after hypnotherapy intervention showed all 45 respondents (100%) with a mild pain scale with a P value of 0.000 (α <0.05). In conclusion, hypnotherapy intervention can significantly reduce or eliminate pain during arteriovenous fistula cannulation in haemodialysis